(untitled) (Lundiana: International Journal of Biodiversity, 2013)
Ambrysus (Ambrysus) wichi sp. nov. is described and illustrated from northwestern Argentina and compared with its close relative A. (A.) kolla López Ruf. The chorionic structure of the egg of A. wichi is described and SEM photographs are presented. The chorion of the egg is a taxonomic character useful in identifying species of Ambrysus.